The Effectiveness of the Think Talk Write Model and Genre Based Approach Assisted by Disaster Videos in Learning to Write Argumentative Texts - Cahyani Ismi Azizah; Muhammad Badrus Siroj (Raja Zulkarnain Education Foundation, 2026)
Learning to write argumentative texts requires a learning model that can develop critical thinking skills and systematic argumentation skills. The Think Talk Write (TTW) and Genre Based Approach (GBA) models, assisted by video, are believed to be effective in teaching argumentative writing skills. This study aims to determine the effectiveness of the TTW and GBA models, assisted by video, in teaching argumentative writing. The research used a quantitative method with a quasi-experimental design, conducted at SMP Diponegoro 7 Gumelar, involving two classes as the research sample. Data were gathered through argumentative text writing tests and analyzed using the Wilcoxon test and the Mann-Whitney U test because the data did not meet the assumptions of normality and homogeneity. The results showed that learning with the TTW model, aided by videos, effectively improved students’ ability to write argumentative texts, evidenced by an increase in the average score from 51.47 to 71.18 and the Wilcoxon test result of 0.000 < 0.05. Learning with the GBA model, supported by videos, was also effective, with an increase in the average score from 52.06 to 69.41 and a Wilcoxon test result of 0.000 < 0.05. Furthermore, the TTW model is more recommended because it has a higher average posttest score and mean rank than the GBA model. However, the Mann-Whitney U test results indicate no significant difference in effectiveness between the two learning models, as the significance value exceeds 0.05.